The Latin American society for developmental biology: A successful history - Wappner, Pablo (2021)
The Latin American Society for Developmental Biology (LASDB) is one of the newest societies in this field. However, despite being new, this society already had a highly important impact on the advancement of Developmental Biology across Latin America and globally. From its conception, the society began with the establishment of courses and congresses at the frontiers of knowledge and with the participation of researchers from Latin American countries and other regions, creating an academic and fraternal environment.The first LASDB congress was held in 2003, and recently, in 2019, the LASDB celebrated its tenth meeting, besides the Pan-American congress organized in 2007. Since the creation of this society and throughout its consolidation, the LASDB has been fortunate in receiving the support of highly prominent Developmental Biology societies, with which it has established links and collaboration that have clearly promoted Development Biology not only in Latin America but also in other parts of the world. At this moment, the LASDB looks to the future to continue supporting science in Latin America as it has done up to the present.